Small molecule ligands for α9 * and α7 nicotinic receptors: A survey and an update, respectively - Alessandro Giraudo; Marco Pallavicini; Cristiano Bolchi (Elsevier, 2023)
The α9- and α7-containing nicotinic acetylcholine receptors (nAChRs) mediate numerous physiological and pathological processes by complex mechanisms that are currently the subject of intensive study and debate. In this regard, selective ligands serve as invaluable investigative tools and, in many cases, potential therapeutics for the treatment of various CNS disfunctions and diseases, neuropathic pain, inflammation, and cancer. However, the present scenario differs significantly between the two aforementioned nicotinic subtypes. Over the past few decades, a large number of selective α7-nAChR ligands, including full, partial and silent agonists, antagonists, and allosteric modulators, have been described and reviewed. Conversely, reports on selective α9-containing nAChR ligands are relatively scarce, also due to a more recent characterization of this receptor subtype, and hardly any focusing on small molecules. In this review, we focus on the latter, providing a comprehensive overview, while providing only an update over the last five years for α7-nAChR ligands.